Health-Related Quality of Life and Angina in Fractional Flow Reserve- Versus Angiography-Guided Coronary Artery Bypass Grafting: FARGO Trial (Fractional Flow Reserve Versus Angiography Randomization for Graft Optimization). Issue 6 (June 2021) - Thuesen, Anne Langhoff; Riber, Lars Peter; Veien, Karsten Tange; Christiansen, Evald Høj; Jensen, Svend Eggert; Modrau, Ivy; Andreasen, Jan Jesper; Borregaard, Britt; Junker, Anders; Mortensen, Poul Erik; Jensen, Lisette Okkels
Abstract : Background: In coronary artery bypass grafting (CABG), the use of fractional flow reserve (FFR) is insufficiently investigated. Stenosis assessment usually relies on visual estimates of lesion severity. This study evaluated health-related quality of life (HRQoL) and angina after FFR- versus angiography-guided CABG. Methods: One hundred patients referred for CABG were randomized to FFR- or angiography-guided CABG. In the FFR group, lesions with FFR>0.80 were deferred, while the surgeon was blinded to the FFR values in the angiography group. Before and 6 months after CABG, HRQoL was assessed by the health state classifier EQ-5D of the EuroQoL 5-level instrument and angina status based on the Canadian Cardiovascular Society classification system were registered. Results: Six-month angiography included FFR evaluations of deferred lesions. In total, completed EQ-5D of the EuroQoL 5-level instrument questionnaires were available in 86 patients (43 in the FFR versus 43 in the angiography-guided group). HRQoL was significantly improved and angina significantly decreased from baseline to 6 months after CABG with no difference between the randomization groups. Graft failure rates and clinical outcomes were similar in both groups. Patients with graft failure or FFR<0.80 of the previous deferred lesions had significantly lower visual analogue scale scores (78.7±14.2 versus 86.8±14.7, P =0.004) and more angina compared with patients without graft failure or FFR≥0.80 at 6-month follow-up. Conclusions: FFR- versus angiography-guided CABG demonstrated similar improvements in HRQoL and angina 6 months after CABG. Graft failure or low FFR in deferred lesions were associated with low HRQoL and angina. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02477371